Nlrp3 Increases the Host’s Susceptibility to Tularemia - Suresh, Ragavan V.; Bradley, Elizabeth W.; Higgs, Matthew; Russo, Vincenzo C.; Alqahtani, Maha; Huang, Wiehua; Bakshi, Chandra Shekhar; Malik, Meenakshi (Frontiers in Microbiology, 2021)
Francisella tularensis (F. tularensis) is a Gram-negative, intracellular bacterium and the causative agent of a fatal human disease known as tularemia. The CDC has classified F. tularensis as a Tier 1 Category A select agent based on its ease of aerosolization, low infectious dose, past use as a bioweapon, and the potential to be used as a bioterror agent. Francisella has a unique replication cycle. Upon its uptake, Francisella remains in the phagosomes for a short period and then escapes into the cytosol, where the replication occurs. Francisella is recognized by cytosolic pattern recognition receptors, Absent In Melanoma 2 (Aim2) and Nacht LRR and PYD domains containing Protein 3 (Nlrp3). The recognition of Francisella ligands by Aim2 and Nlrp3 triggers the assembly and activation of the inflammasome. The mechanism of activation of Aim2 is well established; however, how Nlrp3 inflammasome is activated in response to F. tularensis infection is not known. Unlike Aim2, the protective role of Nlrp3 against Francisella infection is not fully established. This study investigated the role of Nlrp3 and the potential mechanisms through which Nlrp3 exerts its detrimental effects on the host in response to F. tularensis infection. The results from in vitro studies demonstrate that Nlrp3 dampens NF-kB and MAPK signaling, and pro-inflammatory cytokine production, which allows replication of F. tularensis in infected macrophages. In vivo, Nlrp3 deficiency results in differential expression of several genes required to induce a protective immune response against respiratory tularemia. Nlrp3-deficient mice mount a stronger innate immune response, clear bacteria efficiently with minimal organ damage, and are more resistant to Francisella infection than their wild type counterparts. Together, these results demonstrate that Nlrp3 enhances the host’s susceptibility to F. tularensis by modulating the protective innate immune responses. Collectively, this study advances our understanding of the detrimental role of Nlrp3 in tularemia pathogenesis.